Cancer screening prevalence and preference among hospitalized women with and without diabetes mellitus - Margaret A. Mallari; Amteshwar Singh; Jocelyn Shubella; Waseem Khaliq (PLoS ONE, 2025)
Objective To determine the prevalence of nonadherence to breast cancer and colorectal cancer screening, associated risk factors, and screening preference among hospitalized women with and without diabetes aged 50–75 years who were cancer-free at baseline. Methods A prospective study compared women with and without diabetes who were cancer-free (except for skin cancer) at baseline and between 50 and 75 years of age, admitted to the general medical service at an academic center were approached for study participation from December 1, 2014, to May 31, 2017. The study evaluated breast and colorectal cancer screening nonadherence prevalence, preference for screening locale, sociodemographic and clinical variables associated with nonadherence using multivariable logistic regression model. Results Of 510 women, 39% had a prior diagnosis of diabetes mellitus, and 36% were African American. Women with diabetes were more likely to have obesity, reliance on assistive devices for ambulation, inability to work (have a disability), and a greater average number of comorbidities compared to women without diabetes. Women with or without diabetes were equally nonadherent with BRC (28% vs 36%, p = 0.6) and CRC (25% vs 28%, p = 0.51) screening guidelines. After adjustment for sociodemographic and clinical risk factors, only high risk for CRC (OR = 3.20, 95%CI; 1.03–9.91) was an independent risk factor associated with nonadherence to BRC among hospitalized women with diabetes. Whereas after similar adjustment, age younger than 60 years (OR = 2.91, 95%CI; 1.15–7.35) and current or prior smoking (OR = 2.80, 95%CI; 1.14–6.86) were associated with nonadherence to CRC among women with diabetes. 46% of women with diabetes expressed a preference for in-hospital screening for BRC, while 45% expressed a similar preference for CRC. Conclusion Hospitalizations may offer additional screening opportunities as almost half of the women with diabetes preferred undergoing breast and colorectal cancer screening during a hospital stay.